Biochemical findings in sarcoidosis. Issue 6 (June 1980) - Studdy, P R; Bird, R; Neville, E; James, D G
Abstract : The majority of patients with sarcoidosis in this large series have had a number of biochemical investigations performed. Abnormal calcium metabolism was demonstrated in 40% of the patients but permanent renal damage due to nephrocalcinosis as a result of persistent derangement of calcium metabolism was rare. Raised immunoglobulin levels were seen. Half the white and two-thirds of the West Indian patients had elevated IgG levels. Abnormal immunoglobulin levels carried no obvious diagnostic or prognostic significance. Raised alkaline phosphatase levels reflected space-occupying hepatic granulomas and occurred in 23% of patients. Serum angiotensin converting enzyme (SACE) was elevated in half the patients. The highest SACE activity was found in patients with severe parenchymal lung infiltration due to sarcoidosis, and the lowest levels in those with inactive disease or after successful management with steroid drugs. SACE levels were not significantly elevated in four other granulomatous conditions: Crohn's disease, primary biliary cirrhosis, Hodgkin's disease, and active tuberculosis.